2020
DOI: 10.1186/s12880-020-00486-z
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of soft tissue and bone sarcomas from benign lesions utilizing 18F-FDG PET/CT-derived parameters

Abstract: Background Accurate differentiation between malignant and benign changes in soft tissue and bone lesions is essential for the prevention of unnecessary biopsies and surgical resection. Nevertheless, it remains a challenge and a standard diagnosis modality is urgently needed. The objective of this study was to evaluate the usefulness of 18 F-fluorodeoxyglucose ( 18 F-FDG) PET/CT-derived parameters to differentiate soft tissue sarcoma (STS) and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…Additionally, Chen et al presented a regression model using SUVmax and a heterogeneity factor (calculated from a metabolism volume-threshold function from 40% to 80%) and found that it showed diagnostic performance superior to that of individual volumetric parameters. [ 19 ] Im et al reported that the MTV and TLG obtained using a liver-based threshold (liver SUVmean + 2 SDs) were the parameters with the most statistically significant predictive value for event-free survival (hazard ratios = 11.774 and 13.121, respectively, at posttherapy). [ 13 ] We evaluated the MTV and TLG using a liver-based threshold, which would be less influenced by the variability in SUV measurements caused by multiple PET/CT systems.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Chen et al presented a regression model using SUVmax and a heterogeneity factor (calculated from a metabolism volume-threshold function from 40% to 80%) and found that it showed diagnostic performance superior to that of individual volumetric parameters. [ 19 ] Im et al reported that the MTV and TLG obtained using a liver-based threshold (liver SUVmean + 2 SDs) were the parameters with the most statistically significant predictive value for event-free survival (hazard ratios = 11.774 and 13.121, respectively, at posttherapy). [ 13 ] We evaluated the MTV and TLG using a liver-based threshold, which would be less influenced by the variability in SUV measurements caused by multiple PET/CT systems.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies on TIs reporting that MTV, TLG, or both are useful parameters in distinguishing malignant lesions from benign ones[ 27 - 31 ], while other reported different conclusions[ 32 ]. The roles of MTV and TLG in other cancers are still open to debate[ 33 - 36 ]. In this study, both MTV and TLG were not useful in the discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…The best imaging technique in differentiating benign masses from their malignant counterpart (myxoma vs. myxosarcoma, fibroma vs. fibrosarcoma, angioma vs. angiosarcoma and so on) is PET/CT, which is based on the metabolic activity of the tissues: using 18‐Fluorodeoxiglucose ( 18 FDG), a high maximum standardized uptake (SUVmax) and intratumoral glucose metabolic heterogeneity factor (HF) may discriminate well between malignant (sarcomas, lymphomas, or other malignant tumors) and benign masses, as well as in differentiating a tumor thrombus from a simple thrombus. 105 , 106 , 107 , 108 , 109 , 110 To improve the sensitivity and specificity of 18 FDG in the particular setting of cardiac tumors, the physiologic glucose uptake by the myocardium must be minimized. This can be obtained with a low‐carbohydrate, high‐fat diet and with the administration of 50 Units/Kg of body weight of unfractioned heparin before the injection of 18 FDG.…”
Section: Integrating the Echocardiographic Information In A Clinical ...mentioning
confidence: 99%